Pengaruh Modal Usaha dan Beban Promosi Terhadap Laba pada UMKM di Kecamatan Tajur Halang Kabupaten Bogor - Bunga Fatma Nur; Miranti Handayani (LPPM Universitas Bina Sarana Informatika, 2025)
This study was inspired by the observation that many Micro, Small, and Medium Enterprises (MSMEs) in suburban areas continue to face challenges in maximizing their profits, even though they have access to capital and actively conduct promotional activities. The main objective of this research is to analyze the influence of working capital and promotional expenditures on the profitability of MSMEs operating in Tajur Halang Subdistrict, Bogor Regency. The study utilizes primary data obtained from respondents through an online questionnaire distributed via Google Forms. Using the Slovin formula, a sample of 86 respondents was determined. The analytical methods applied include classical assumption tests, multiple linear regression analysis, and hypothesis testing using SPSS version 27. The results of the analysis reveal that: (1) the t-count value for business capital exceeds the t-table value, indicating that business capital significantly affects profit; (2) the t-count value for promotional expenses is lower than the t-table value, suggesting that promotional expenses do not significantly affect profit; and (3) both business capital and promotional expenses have a simultaneous significant effect on profit, as shown by the F-count value being higher than the F-table value. This result shows that while promotional costs have little effect on profits in MSMEs in the suburbs, efficient capital management is a crucial component of raising profitability. The uniqueness of this study stems from its integration of financial and marketing variables within the context of suburban MSMEs, offering valuable insights for developing strategies to improve profitability and ensure long-term business sustainability